Spatial Distribution Analysis of Land Use, Land Surface Temperature, and Temperature-Humidity Index in Bogor City in 2004, 2014, and 2024 - Gustiawan, Ridho; Hermawan, Erwin; Kamilah, Nurul; Primasari, Dewi (Universitas Lampung, 2025)
Rapid urbanization in Bogor City in 2004, 2014, and 2024 caused significant changes in land use, marked by an increase in built-up areas and a decrease in vegetation cover. These changes triggered an increase in Land Surface Temperature (LST) and Temperature Humidity Index (THI), which had an impact on heat stress, health disorders, and a decline in quality of life. This study analyzes the relationship between land use changes and LST and THI and develops an interactive web application for visualization. Land classification was performed using the Random Forest algorithm, LST was calculated from Landsat thermal bands (TM 2004, OLI/TIRS 2014 & 2024), and THI was based on Air Temperature (T(a) )and Relative Humidity (RH). The results show that built-up land increased by 2,074 ha (from 4,371 ha to 6,445 ha), in line with an increase in average LST from 26.16°C to 27.13°C and THI from 24.30 to 24.90. In conclusion, the increase in built-up area contributed significantly to the rise in LST and THI, emphasizing the importance of sustainable spatial planning, such as optimizing green open spaces to maintain thermal comfort and quality of life.Keywords: